Mass spectrometric analysis of cyclofenil and its metabolites in human urine - Myung, SW; Min, HK; Kim, DH; Kim, M; Cha, S; Yoo, EA; Yim, YH (JOHN WILEY & SONS LTD, 2002)
Using gas chromatography/electron impact-mass spectrometry (GC/EI-MS) and high performance liquid chromatography with atmospheric pressure chemical ionization tandem mass spectrometry (HPLC/APCI-MS/MS), the structures of cyclofenil metabolites in human urine have been assigned. The hydroxyl metabolites liberated from the glucuronide conjugates after acid hydrolysis were characterized as the trimethylsilyl (O-TMS) derivatives using GC/MS. The conjugate glucuronide forms were detected without hydrolysis by HPLC/MS. Cyclofenil was not observed in urine. Tentative structures for the two metabolites are proposed. Copyright (C) 2002 John Wiley Sons, Ltd.